2018
DOI: 10.1063/1.5012857
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon-induced demagnetization and magnetic switching in nickel nanoparticle arrays

Abstract: We report on the manipulation of magnetization by femtosecond laser pulses in a periodic array of cylindrical nickel nanoparticles. By performing experiments at different wavelength, we show that the excitation of collective surface plasmon resonances triggers demagnetization in zero field or magnetic switching in a small perpendicular field. Both magnetic effects are explained by plasmon-induced heating of the nickel nanoparticles to their Curie temperature. Model calculations confirm the strong correlation b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…The combination of plasmon-induced heating by light with ferromagnetic nanoislands enables one to overcome limitations imposed by the grain size. Studies in this direction were also reported by Kataja et al [168], who reported on the manipulation of magnetization by femtosecond laser pulses in a periodic array of cylindrical nickel nanoparticles. They showed a strong correlation between the excitation of SLRs and changes in magnetization.…”
Section: Far-field Diffractive Coupling In Magneto-plasmonic Crystalssupporting
confidence: 53%
“…The combination of plasmon-induced heating by light with ferromagnetic nanoislands enables one to overcome limitations imposed by the grain size. Studies in this direction were also reported by Kataja et al [168], who reported on the manipulation of magnetization by femtosecond laser pulses in a periodic array of cylindrical nickel nanoparticles. They showed a strong correlation between the excitation of SLRs and changes in magnetization.…”
Section: Far-field Diffractive Coupling In Magneto-plasmonic Crystalssupporting
confidence: 53%
“…An X-ray diffraction study by Graves et al [224] on GdFeCo showed that a composition inhomogeneity could lead to local variations in the switching 51 behavior. A different investigation was made by Kataja et al [225], who could observe both plasmoninduced demagnetization and magnetic switching in a Ni nanoparticle array, excited by a femtosecond laser pulse, which they explained by the plasmonic local heating of the nanoparticles above the Curie temperature. A next step in this direction could be the fabrication of GdFeCo nanoparticle arrays.…”
Section: Opto-magnetism: Towards An Ultrafast Control Of Magnetismentioning
confidence: 97%
“…26 Potential applications of magnetoplasmonic nanostructures include nonreciprocal optical devices, 27 label-free biosensors, 28,29 metrology, 30 and ultrafast all-optical magnetic switching. 31 However, ohmic losses in ferromagnetic metals are considerably larger than those in noble metals, and the narrowing of intrinsically broad resonances via a transition to lasing has not been demonstrated yet.…”
mentioning
confidence: 99%